Expandable distal femur megaprosthesis: A European Musculoskeletal Oncology Society study on 299 cases. Issue 4 (7th June 2020) - Staals, Eric Lodewijk; Sambri, Andrea; Campanacci, Domenico Andrea; Muratori, Francesco; Leithner, Andreas; Gilg, Magdalena Maria; Gortzak, Yair; Van De Sande, Michiel; Dierselhuis, Edwin; Mascard, Eric; Windhager, Reinhard; Funovics, Philipp; et al.
Abstract: Background and Objectives: Expandable distal femur prostheses have become more popular over the last decades, but scientific data is limited. Methods: A retrospective study was performed, including cases treated between 1986 and 2019 in 15 European referral centers for bone sarcomas. Results: A total of 299 cases were included. Average follow‐up was 80 months (range, 8‐287 months). Mean patient age was 10 years. Most (80%) of the implants were noninvasive growers and a fixed hinge knee was used more often (64%) than a rotating hinge. Most prosthetic designs showed good (>80%) implant survival at 10 years, but repeat surgery was required for 63% of the patients. The most frequent reason for revision procedure was the completion of lengthening potential. Noninvasive expandable implants showed less risk of infection compared to invasive growers (11.8% vs 22.9% at 10 years). No difference in aseptic loosening was found between cemented and uncemented stems. Conclusions: This study shows the increasing popularity of expandable distal femur prostheses, with overall good results for function and implant survival. However, repeat surgery is frequently required, especially in patients under the age of 10 years old. Infection is less frequent in noninvasive growers compared to implants that require invasive lengthening procedures.